2014
DOI: 10.1002/ijc.29134
|View full text |Cite
|
Sign up to set email alerts
|

A brief history of cancer: Age‐old milestones underlying our current knowledge database

Abstract: This mini-review chronicles the history of cancer ranging from cancerous growths discovered in dinosaur fossils, suggestions of cancer in Ancient Egyptian papyri written in 1500-1600 BC, and the first documented case of human cancer 2,700 years ago, to contributions by pioneers beginning with Hippocrates and ending with the originators of radiation and medical oncology. Fanciful notions that soon fell into oblivion are mentioned such as Paracelsus and van Helmont substituting Galen's black bile by mysterious e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
82
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(91 citation statements)
references
References 32 publications
0
82
0
9
Order By: Relevance
“…The association between inflammation and cancer is widely recognized. In 1863, Rudolf Virchow (3,4) reported that some tumors were infiltrated by inflammatory cells, leading to the hypothesis that inflammation is associated with cancer. In 2012, the International Agency for Research on Cancer established that infection with some pathogens, including Helicobacter pylori, human papillomavirus (VPH) variant 16, and Schistosoma haematobium, is associated with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The association between inflammation and cancer is widely recognized. In 1863, Rudolf Virchow (3,4) reported that some tumors were infiltrated by inflammatory cells, leading to the hypothesis that inflammation is associated with cancer. In 2012, the International Agency for Research on Cancer established that infection with some pathogens, including Helicobacter pylori, human papillomavirus (VPH) variant 16, and Schistosoma haematobium, is associated with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Even before the definition of a gene existed, observations were made that cancer cells have a different shape from normal cells and that disruptions in tissue architecture were symptomatic of cancer-findings which still remain a foundation of cancer pathology (Fig. 1A;Faguet 2015). It is now clear that the expression of oncogenes, or loss of tumor suppressors, affects numerous transcriptional, epigenetic, and post-translational processes, and thus signaling states, to promote cancer cell survival, proliferation, and invasion, and ultimately changes in cell shape ( Fig.…”
mentioning
confidence: 99%
“…Before we continue on the path leading to the development of antibody-drug conjugates as clinical drugs,abrief historical overview of previous paradigms of cancer treatment is in order.T hus,i na ncient times Greek physicians such as Hippocrates of Kosa nd Galen of Pergamon attributed the occurrence of cancer to an excess of "black bile" in the patientsb ody. [11] Tu mors were either left untreated or surgically excised. [12] Thel atter practice was accompanied by an often soon-after relapse of the disease in cases where the tumor was not fully removed.…”
Section: Conventional Cancer Therapeuticsmentioning
confidence: 99%